Clause order in sentences containing a since- subordinate - Bénédicte GUILLAUME (E-REA)
This paper deals with clauses introduced by the subordinator since (hereafter SC’s), and more specifically with their placement in the sentence in relation to the main clause (hereafter MC) on which they depend from a syntactic point of view. The study of a large corpus consisting of nearly five hundred examples sampled from the one-hundred-million-word British National Corpus shows that the placement of an SC (that is to say, whether it precedes or follows its MC) is impossible to predict based solely on the nature of the subordinate, which can be either causal or temporal. Indeed, the postponing of the subordinate turns out to be the more frequent option in both categories, even if it is even more systematic in the case of the temporal SC’s.Several criteria are examined in order to account for the placement of a causal SC, the most decisive of which turns out to be the shift of emphasis generated by the placement of the subordinate. Whenever it precedes the MC, it is the cause and effect relationship between the clauses which is given prominence, while it is the effect more specifically whenever the SC is postponed. Still, this shift is not strongly discriminative from a semantic point of view, which explains why a causal SC could most of the time be displaced without altering the overall meaning of the sentence. As for the temporal SC’s, those concerned primarily with the aspectual determination of the verb phrase in the MC are much more likely to be postponed than fronted. On the other hand, the fronting of a temporal SC is generally brought about by the fact that it is not purely aspectual: although such an SC is mostly temporal, it also provides a justification for the MC in a manner not unlike that observed in the causal SC’s, which accounts for a mixed type of relationship between the SC and the MC, partly temporal and partly causal.The presence or absence of a punctuation mark between the SC and the MC is also taken into account in the analysis of the examples, and attempts are made to account for such variations as well.